2015
DOI: 10.1177/0014402914551742
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Enhanced Anchored Instruction in Inclusive Math Classrooms

Abstract: The Common Core State Standards for Mathematics will place more pressure on special education and math teachers to raise the skill levels of all students, especially those with disabilities in math (MD). The purpose of this study was to assess the effects of enhanced anchored instruction (EAI) on students with and without MD in co-taught general education classrooms. Results showed that students in the EAI condition improved their performance on math skills contained in several of the standards. Effect sizes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 32 publications
1
77
0
2
Order By: Relevance
“…The empirical demonstration comes from a secondary analysis of data from a large‐scale mathematics education research study (Bottge et al., ; Bottge et al., ). The goal of this study was to examine the efficacy of an innovative instructional method called enhanced anchored instruction (EAI; Bottge, Heinrichs, Chan, Mehta, & Watson, ).…”
Section: Empirical Demonstrationmentioning
confidence: 99%
“…The empirical demonstration comes from a secondary analysis of data from a large‐scale mathematics education research study (Bottge et al., ; Bottge et al., ). The goal of this study was to examine the efficacy of an innovative instructional method called enhanced anchored instruction (EAI; Bottge, Heinrichs, Chan, Mehta, & Watson, ).…”
Section: Empirical Demonstrationmentioning
confidence: 99%
“…The discourse of teaching interventions for mathematical engagement This discourse construes inclusion in terms of strategies for including students in mathematics education. Words and phrases signalling interventions are 'schema-based instruction' (Jitendra & Star, 2011); 'interactive groups' (Garcia-Carrión & Diez-Palomar, 2015); 'cognitive guided instruction' (Guðjónsdóttir & Kristinsdóttir, 2011;Hankes, Skoning, Fast, & Mason-Williams, 2013;Moscardini, 2014); 'cluster-based instruction' (Sunardi, Anwar, & Andayani, 2016); 'techno-kinaesthetic visually based activities' (Tabur, 2014); 'cognitive strategy instruction on math problem-solving' (Montague, Enders, & Dietz, 2011); 'problem-solving procedures' (Fletcher, 2014); 'explicit instruction' (Hinton, Flores, Schweck, & Burton, 2016); 'simultaneous prompting procedure' (Heinrich, Knight, Collins, & Spriggs, 2016); 'universal design for learning' (Hunt & Andreasen, 2011;Lambert & Stylianou, 2013); 'anchored instruction' (Bottage et al, 2015;Mannheimer Zydney, Bathke, & Hasselbring, 2014); 'prompting' (Davenport & Johnston, 2015); 'regulated learning strategies' (Ness & Middleton, 2012); 'teacher coaching' (Duchaine, Jolivette, & Fredrick, 2011); and 'use of math apps' (Zhang, Trussell, Gallegos, & Asam, 2015).…”
Section: Operationalisation Of the Notion Of Inclusion In Mathematicsmentioning
confidence: 99%
“…More recently, Bottge et al. () successfully employed enhanced anchored instruction using computer‐based activities, video‐based anchored problems, applied projects, and explicit instruction to teach secondary students with a learning disability problem solving, geometry, fractions, and proportions. In addition to these studies, other variations of video‐based interventions, such as video modeling, were shown to be effective for teaching students with a learning disability in mathematics.…”
Section: Strategies For Teaching Students With Learning Disabilitymentioning
confidence: 99%
“…For example, Bottge and associates successfully used contextualized instruction within videos (i.e., anchored instruction) to teach secondary students with a learning disability problem solving (Bottge, 1999;Bottge, Heinrichs, Mehta, & Hung, 2002), pre-algebra (Bottge, Heinrichs, Chan, & Serlin, 2001), and geometry (Bottge, Heinrichs, Chan, Mehta, & Watson, 2003). More recently, Bottge et al (2015) successfully employed enhanced anchored instruction using computer-based activities, video-based anchored problems, applied projects, and explicit instruction to teach secondary students with a learning disability problem solving, geometry, fractions, and proportions. In addition to these studies, other variations of video-based interventions, such as video modeling, were shown to be effective for teaching students with a learning disability in mathematics.…”
Section: Strategies For Teaching Students With Learning Disabilitymentioning
confidence: 99%